1994
DOI: 10.3109/00498259409043293
|View full text |Cite
|
Sign up to set email alerts
|

Placental transfer, lacteal transfer and plasma protein binding of gemcitabine

Abstract: 1. The placental transfer, lacteal transfer and plasma protein binding of gemcitabine have been studied in rat and dog after single intravenous administration of 10 mg/kg 14C-gemcitabine. 2. Radioactivity was distributed to the foetuses at 5 min after administration to rat on days 12 and 18 of gestation. The concentrations of radioactivity in the foetal liver, lung and kidney on day 18 of gestation were 4.0-6.4 times higher than in the maternal blood at 4 h after administration. Relatively high levels of radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…The few available studies show that gemcitabine in plasma is freely available for intracellular transport as it is minimally plasma protein bound, with reported plasma protein binding values ranging from −2.5% to 7% (Shipley et al. , 1992; Esumi et al. , 1994a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The few available studies show that gemcitabine in plasma is freely available for intracellular transport as it is minimally plasma protein bound, with reported plasma protein binding values ranging from −2.5% to 7% (Shipley et al. , 1992; Esumi et al. , 1994a).…”
Section: Introductionmentioning
confidence: 99%
“…Limited pharmacokinetic (PK) studies have been conducted with gemcitabine in dogs. The few available studies show that gemcitabine in plasma is freely available for intracellular transport as it is minimally plasma protein bound, with reported plasma protein binding values ranging from )2.5% to 7% (Shipley et al, 1992;Esumi et al, 1994a). Elimination of gemcitabine occurs primarily through deamination by cytidine deaminase to the inactive metabolite 2¢,2¢-difluorodeoxyuridine (dFdU), which is then excreted in the urine (Shipley et al, 1992;Bouffard et al, 1993;Kawai et al, 1995;Plunkett, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental animal studies have demonstrated that gemcitabine had both embryotoxic and fetotoxic effects, characterized by cleft palate, incomplete ossification, fusion of pulmonary artery, absence of gall bladder, decreased fetal viability, and developmental delays [16,17]. As of today, there is no report describing the outcome in humans receiving gemcitabine during pregnancy.…”
Section: Discussionmentioning
confidence: 93%
“…After confirming that our IN drug delivery technique targeted the OE without toxicity to target and non-target tissues, we then used in vivo brain microdialysis to investigate the potential for PV to enhance delivery of IN-administered gemcitabine, a model nucleoside chemotherapeutic drug (Santoro et al, 2000; De Lange et al, 2004), to the CNS. Gemcitabine, our model drug, is a small (MW 299.66) polar molecule and has 7% plasma protein binding ratios in rat and dog and 10% in human (Esumi et al, 1994). Since it is a small hydrophilic molecule, it can be transported across the nasal epithelial TJs by paracellular transport.…”
Section: Introductionmentioning
confidence: 99%